PERSEBARAN PRASASTI-PRASASTI BERBAHASA MALAYU KUNA DI PULAU JAWA - Richadiana Kartakusuma (BRIN, 1999)
In the context of culture, Old Malay inscriptions do not stand alone, but are in certain conditions according to their era. In other words, the inscription is a structural unity, covering the socio-cultural realities in the relationship between people. Although it is undeniable that there may be infrastructure elements such as mindset, values and living arrangements as the main elements that characterize the culture of origin (Old Malay).